Proposed Decisions to Modify the New Arrangements to Borrow and to Extend the Deadline for a Review of the Borrowing Guidelines. (Policy Papers; Policy Paper ;, 2020)
This paper presents a proposal for reforming the NAB with a doubling of the aggregate size of the NAB and amendments to the NAB Decision. The proposal contains the following key elements: doubling the aggregate size of NAB credit arrangements, through a doubling of all current NAB credit arrangements; establishing a new NAB period, extending from January 1, 2021 through end-2025; updating the NAB Decision as some provisions have become obsolete or outdated; and including a new provision in the NAB Decision limiting the activation of bilateral borrowing during the new NAB period. The paper also proposes a 6-month extension of the deadline for the review of the Guidelines for Borrowing by the Fund to end-June 2020.